ARTIFICIAL INTELLIGENCE AND HUMAN IDENTITY:ETHICAL CHALLENGES IN ISLAMIC THOUGHT (Contemporary Journal of Social Science Review, 2025)
This article critically examines the ethical challenges posed by the rapid advancement of Artificial Intelligence (AI) to human identity, consciousness, and moral agency from the perspective of Islamic thought. As artificial intelligence increasingly emulates human cognitive and decision-making abilities, it raises profound questions concerning the limits of khilāfah (human vicegerency), taklīf (moral responsibility), and ethical accountability. The study situates AI as a transformative technology capable of simulating human cognitive functions while emphasizing the intrinsic limitations of machine intelligence in replicating the human soul (rūḥ), moral intentionality (niʿyah), and ethical discernment. Drawing on classical Islamic sources, including the Qur’ān, Hadith, and the works of scholars such as Al-Ghazālī, Ibn Miskawayh, and Al-Qurṭubī, the article analyzes the foundational principles of Islamic ethics Maṣlaḥah (public welfare), ʿAdl (justice), Amānah (trust), and Niʿyah (intention) and their application to contemporary AI systems. Key ethical concerns addressed include autonomy, accountability, privacy, bias, and the preservation of human dignity within technologically mediated environments. The article further employs the Maqāṣid al-Sharīʿah framework to evaluate the alignment of AI technologies with the objectives of Islamic law, ensuring the protection of faith, life, intellect, lineage, and property. By integrating classical jurisprudential reasoning with modern AI ethics, the study proposes a normative framework for the responsible development and deployment of AI in Muslim societies, highlighting the necessity of maintaining human-centered moral agency while leveraging AI’s potential to enhance societal welfare. This research contributes to the emerging discourse at the intersection of technology, ethics, and Islamic thought, providing scholars, policymakers, and technologists with a comprehensive framework to navigate the ethical complexities of AI. Also engages both classical and contemporary Islamic ethical paradigms to explore whether AI possesses any capacity for moral reasoning or merely functions as a tool within the scope of human agency. By unpacking these complexities, the paper aims to enrich Islamic philosophical discourse on how technological advancement can coexist with the preservation of human dignity and the realization of divine purpose.